Neuropsychological and quality of life outcomes in PKU patients: expert recommendations of assessment tools in Brazil - Schwartz, Ida Vanessa Doederlein; Quesada, Andrea Amaro; Ribeiro, Erlane Marques; Martins, Ana Maria; Vilela, Daniel Reda Fenga; Pessoa, André (Arquivos de Neuro-Psiquiatria, 2023)
Background Phenylketonuria (PKU) is an inborn error of metabolism caused by deficient activity of phenylalanine hydroxylase. In Brazil, the National Neonatal Screening Program enables early treatment of patients with PKU, which prevents them from developing severe neurological damage and mental disabilities. However, between 20 and 30% of early-treated patients with PKU present focal cognitive deficits, including deficits in working memory, processing speed, and psychiatric symptoms such as anxiety, depression, and attention deficit hyperactivity disorder (ADHD). Therefore, age-specific neuropsychiatric and cognitive tests are important components of PKU patient care. To date, there are no officially approved guidelines or recommendations of tools in Portuguese validated for use in Brazil that could be applied to assess these parameters in patients with PKU.Objective To recommend tools validated for use in Brazil that can be used in daily clinical practice to assess quality of life and neuropsychological outcomes in patients with PKU.Methods Six Brazilian experts discussed about eligible tools based on their clinical experience, the feasibility of their use in clinical routines, and their availability in public health services. Before the meeting, an independent review of the literature was conducted to identify the currently validated tools in Brazil, using the MEDLINE and SciELO databases.Results The experts recommended nine tools to assess quality of life (Peds-QL, SF-36 or WHOQOL-bref), executive function (BRIEF or Bayley-III), IQ (SONR 2½-7[a] or WASI) and ADHD (MTA-SNAP-IV and ASRS).Conclusion These instruments may be easily incorporated into clinical practice and improve the quality of multidisciplinary care of patients with PKU.
Keywords: Phenylketonurias; Mental Health; Neuropsychological Tests; Quality of Life; Brazil